2010
DOI: 10.1017/s1481803500012240
|View full text |Cite
|
Sign up to set email alerts
|

The utility of renal ultrasonography in the diagnosis of renal colic in emergency department patients

Abstract: Objective: Computed tomography (CT) is an imaging modality used to detect renal stones. However, there is concern about the lifetime cumulative radiation exposure attributed to CT. Ultrasonography (US) has been used to diagnose urolithiasis, thereby avoiding radiation exposure. The objective of this study was to determine the ability of US to identify renal colic patients with a low risk of requiring urologic intervention within 90 days of their initial emergency department (ED) visit. Methods: We completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…This is higher than most of the studies done previously, Yan et al (1.55:1), Edmonds et al (1.14:1) and Kobayashi et al (1.68:1).9-11 Microscopic hematuria was seen in only 31% of the patients in the current study, which is much lower as compared to Yan et al (78.5%), Edmonds et al (60.3%), and Kobayashi et al (44.2%). [9][10][11] The mean age of presentation is lower in the current study (40.2), though the findings are similar to studies conducted by Edmonds at al where the age of presentation is 41.6 years of age. However, Kobayashi et al observed higher mean age (47.1).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is higher than most of the studies done previously, Yan et al (1.55:1), Edmonds et al (1.14:1) and Kobayashi et al (1.68:1).9-11 Microscopic hematuria was seen in only 31% of the patients in the current study, which is much lower as compared to Yan et al (78.5%), Edmonds et al (60.3%), and Kobayashi et al (44.2%). [9][10][11] The mean age of presentation is lower in the current study (40.2), though the findings are similar to studies conducted by Edmonds at al where the age of presentation is 41.6 years of age. However, Kobayashi et al observed higher mean age (47.1).…”
Section: Discussionsupporting
confidence: 87%
“…However, Kobayashi et al observed higher mean age (47.1). [9][10][11] The ureteric calculus was most common in the VUJ (43%) and lower ureter (24%), and least common in mid ureter (13%) as observed on USG. The mean ureteric stone size was 7.2mm and serum creatinine levels were 0.85mg/dl which are similar to findings in other studies (Table 4).…”
Section: Discussionmentioning
confidence: 96%
“…This often indicated calculi are present with a sensitivity nearing one hundred percent (Edmonds, Yan, Sedran, McLeod, & Theakston, 2010). The study took place at a multi-campus academic teirtary care center in Ontario, Canada.…”
Section: Ultrasonographymentioning
confidence: 99%
“…This has been suggested for the investigation of appendicitis and urolithiasis. 10,11 When nonionizing imaging modalities are not feasible, the next best option is a test that minimizes radiation exposure.…”
Section: ])mentioning
confidence: 99%